Influence of tree cover on herbaceous layer development and carbon and water fluxes in a Portuguese cork-oak woodland - Dubbert, Maren; Mosena, Alexander; Piayda, Arndt; Cuntz, Matthias; Correia, Alexandra Cristina; Pereira, João Santos; Werner, Christiane (Acta Oecologica, 2014)
Facilitation and competition between different vegetation layers may have a large impact on small-scale vegetation development. We propose that this should not only influence overall herbaceous layer yield but also species distribution and understory longevity, and hence the ecosystems carbon uptake capacity especially during spring. We analyzed the effects of trees on microclimate and soil properties (water and nitrate content) as well as the development of an herbaceous community layer regarding species composition, aboveground biomass and net water and carbon fluxes in a cork-oak woodland in Portugal, between April and November 2011. The presence of trees caused a significant reduction in photosynthetic active radiation of 35molm−2d−1 and in soil temperature of 5°C from April to October. At the same time differences in species composition between experimental plots located in open areas and directly below trees could be observed: species composition and abundance of functional groups became increasingly different between locations from mid April onwards. During late spring drought adapted native forbs had significantly higher cover and biomass in the open area while cover and biomass of grasses and nitrogen fixing forbs was highest under the trees. Further, evapotranspiration and net carbon exchange decreased significantly stronger under the tree crowns compared to the open during late spring and the die back of herbaceous plants occurred earlier and faster under trees. This was most likely caused by interspecific competition for water between trees and herbaceous plants, despite the more favorable microclimate conditions under the trees during the onset of summer drought.
Keywords: carbon fluxes; competition; Facilitation; Mediterranean; Plant interactions; Understory; water fluxes

Validación de productos MODIS relacionados con la estimación de flujos de carbono en una dehesa - Durá, E.; Mendiguren, G.; Pacheco, J.; Martín, M. P.; Riaño, D.; Iturrate, M.; Gimeno, C.; Carrara, A. (XV Congreso Nacional de Tecnologías de la Información Geográfica, Madrid, AGE-CSIC, 19-21 de Septiembre de 2012, 2012)
Several studies have demonstrated the potential of the images obtained by MODIS TERRA and AQUA platforms for global analysis of parameters related to the structure and functioning of vegetation critical for estimating and modeling the water and carbon exchanges between the biosphere and atmosphere at a global scale. However, recent works have revealed the existence of large errors (Pisek et al., 2007, Sea et al., 2011) showing that some products lack the robustness and consistency required, particularly for drought prone ecosystems with a complex structure of vegetation, such as Mediterranean ecosystems The main objective of this study is the validation of MODIS TERRA and AQUA products using field measurements in order to quantify the possible differences and analyze their potential causes. We have analysed a series of MOD/MYD13, MOD/MYD15, MOD/MYD17products acquired between 2009 and 2011 in a “dehesa” located in Caceres province which has an "eddy covariance" tower included in the FLUXNET international network. These results show low correlation for LAI (Leaf Area Index) (r2 = 0.67), but high correlation for NDVI (Normalized Difference Vegetation Index) (r2 = 0.92) and gross primary productivity or GPP (r2 = 0.80). However, although MODIS collects fine temporal dynamics of flows and structural changes in the ecosystem, there are some important differences between MODIS products, including NDVI and GPP, and terrain data
The following values have no corresponding Zotero field: periodical: XV Congreso Nacional de Tecnologías de la Información Geográfica, Madrid, AGE-CSIC, 19-21 de Septiembre de 2012
Keywords: carbon fluxes; Dehesa; MODIS products; validation